DINAMIKA FLUIDA LAPIS TIPIS DI SEKELILING KABEL AKIBAT PENGARUH GRAVITASI, ANGIN, DAN TEGANGAN - ANDIS , NOFRI
Thin water lm around cable conduces asymmetrical of cable cross section. As the wind involved, this asymmetrical condition will create vibration through the cable. Gravitation, wind, and surface tension are some of the factors that in-